Keberadaan Bentos: Larva Insekta di Salah Satu Sungai di Indonesia (Jurnal Bioconcetta, 2017)
There is sand excavation activity by using the machine can destruct the river substrate which effect to the life of the benth: insecta larvae would be hampered. The presence of benth is strongly influenced by the very significant physical-chemical and biological conditions of water to determine the type and density of benth populations in the waters. This study aims to determine the composition of benth: insects larvae in one of the rivers in Indonesia. This research is a case survey research. Sampling is done by setting three research stations and each station has three points of observation. Sampling at three points of observation was done twice. The results showed that the composition of benth found consisted of 3 classes, 9 orders, 14 families and 14 genera, benth diversity index ranged from 0.8691-1.7200, the physical condition of the waters under normal conditions is temperature 23-25oC, degree of acidity (pH) range between 5,93-66, dissolved oxygen (DO) 3,26-5,37 mg/L, while the aquatic chemical condition is not in normal condition is suspended solids content 19-112 mg/L